The globalized woman : reports from a future of inequality - Wichterich, Christa (North Melbourne : Spinifex Press ; London ; New York : Zed Books, 2000)
"Demonstrating exactly how women, all over the world, have become the call-girls of the global labour market, the author of this book uses a mixture of case studies, examples and quotations to illustrate some hard facts. She looks at women across the world - to show how their lives have been turned upside down by industrialization in the South and a return to homeworking in the North. We meet Martha, 17-year old mother of two in Harlem, who cannot afford medical provision on the salary she has been forced to accept; Margaret, former secretary at the Ministry of Agriculture in Nairobi, now trading in second-hand clothes; Li Thi, a Vietnamese woman who is paid $500 a year for stitching the same running shoes that a top US basketball player is paid $20 million a year to promote." "From New York to Phnom Penh, from Moscow to Dakar, we see the devastating effects of the unfettered power of transnational corporations on women's lives. This book charts that devastation and calls for urgent action - by states across the world and by women themselves."--BOOK JACKET.
Machine derived contents note: Table of contents for The globalized woman : reports from a future of inequality / Christa Wichterich ; translated by Patrick Camiller. -- Bibliographic record and links to related information available from the Library of Congress catalog -- Information from electronic data provided by the publisher. May be incomplete or contain other coding. -- The Global Conveyor Belt -- Worldwide Service -- Means of Living -- Women in the Wreckage of Structural Adjustment or The Feminisation of Social Security -- Variants of Modernity -- The Globalisation of Women's Movements -- Library of Congress subject headings for this publication: Women Employment, Unemployed women workers, Labor market, Competition, International, International division of labor.
Includes bibliographical references (p. [170]-172) and index.
Keywords: Women -- Employment; International division of labor; Unemployed women workers; Labor market; Competition, International